Circulating tumor cell clusters are a potential biomarker for detection of non-small cell lung cancer. (August 2019) - Manjunath, Yariswamy; Upparahalli, Sathisha V.; Suvilesh, Kanve N.; Avella, Diego M.; Kimchi, Eric T.; Staveley-O'Carroll, Kevin F.; Li, Guangfu; Kaifi, Jussuf T.
Highlights: Circulating tumor cell clusters are candidates for NSCLC detection. Circulating tumor cell clusters are found in NSCLC patients. Circulating tumor cell clusters are undetectable in screening subjects. Non-clustered circulating tumor cells can be detected in screening subjects. Abstract: Objectives: Circulating tumor cell (CTC) clusters (≥2 CTCs in aggregate) detected in the peripheral blood have predictive value in solid cancers, including non-small cell lung cancer (NSCLC). The goal of the study was to investigate the presence of CTC clusters in NSCLC patients and in high-risk screening subjects having no or benign nodules in a screening low-dose CT (LDCT). Materials and methods: In a prospective pilot trial, 7.5 ml peripheral blood was collected from treatment-naïve NSCLC patients, LDCT screening subjects (55–80 years, ≥30 pack-year smoking history) with no (Lung-RADS 1) or benign lung nodules (Lung-RADS 2), and healthy never-smoking controls. CTCs were enriched by size, also allowing CTC cluster isolation. For CTC identification and enumeration, immunofluorescence staining was performed for cytokeratins (CK) 8/18 and/or 19, EpCAM, CD45, and nuclei were stained with DAPI. Clinicopathological data were collected, and LDCT interpreted by the American College of Radiology Lung-RADS criteria. Results: CTC clusters were detected in 12/29 (41.4%) of all NSCLC patients, but not found in 31 high-risk screening subjects with Lung-RADS 1 or Lung-RADS 2 ( P < 0.05). Since non-clustered, single CTCs were detectable in both groups of NSCLC patients (100%) and in 18/31 (58.1%) of high-risk screening subjects. No CTCs were detected in 20 healthy control subjects. Conclusion: This pilot study suggests that CTC clusters are a useful and specific liquid biomarker to further explore for screening by LDCT and risk stratification of NSCLC patients. Future prospective studies with higher subject numbers will need to be performed.